Investigation on the occurrence of tles associated positive cloud to ground (+CG) lightning in UMP Pekan - Chan, Hwee Geem (2019)
Lightning is one of the phenomena that occur around the area above the atmosphere. Transient Luminous Events (TLEs) is a type of lightning events which take place above the flash of lightning in a thunderstorm cloud. It is a very fast event that is hardly seen and happens in a very short period of time. So, a high frame-rate capturing device is required to record it. This project studies about the possibility of TLEs occurrences around Universiti Malaysia Pahang (UMP) Pekan campus area by selecting a simple and suitable device to detect the event. There are various types of transient luminous such as Elves, Sprites, Halos, Blue Jets, and Gigantic Jets. By setting a distance radius of 100 km from UMP Pekan with a minimum altitude height of 20 km, the event was traced using a monochrome camera. This allowed the event to be clearly recorded and analysed, namely by the characteristic of categories captured with the video and frame. Sprites are dielectric breakdown at an approximate altitude of 20 km to 95 km and are normally triggered by +CG lightning events. Each of the tracking process results in the possibility of TLE occurrences in the atmosphere of UMP Pekan campus. This result was limited to only a radius of 100 km away from UMP Pekan campus. The study revealed that, TLEs cannot be easily captured. However, an unknown discharge lightning event was found. The unknown event detected was possibly a Carrot Sprite upon comparing all the data obtained with those available in Malaysian Meteorological Department (MMD). Hence, TLEs can be observed around UMP Pekan campus, especially Sprites.